2020
DOI: 10.2147/idr.s224228
|View full text |Cite
|
Sign up to set email alerts
|

<p>A Clinical Review and Critical Evaluation of Imipenem-Relebactam: Evidence to Date</p>

Abstract: Imipenem-relebactam (I-R) is a novel beta-lactam/beta-lactamase inhibitor combination given with cilastatin. It is indicated for the treatment of complicated urinary tract infections, complicated intra-abdominal infections, and hospital-acquired or ventilatorassociated bacterial pneumonia. A literature search was completed to evaluate the evidence to date of I-R. I-R has in vitro activity against multidrug-resistant organisms including carbapenem-resistant Pseudomonas aeruginosa and extended-spectrum beta-lact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 60 publications
0
24
0
1
Order By: Relevance
“…The most striking achievements are the discovery of diazabicyclooctanones (DBOs), non-β-lactam β-lactamase inhibitors [24]. Recently, two DBOs (avibactam and relebactam) have been approved for clinical use in combination with β-lactams such as ceftazidime, imipenem and cilastatin [25][26][27]. Moreover, two novel DBO-type inhibitors, zidebactam and nacubactam, which have high affinity for penicillin-binding protein 2 and potent inhibition of β-lactamase, are under investigation in clinical trials combined with β-lactams [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…The most striking achievements are the discovery of diazabicyclooctanones (DBOs), non-β-lactam β-lactamase inhibitors [24]. Recently, two DBOs (avibactam and relebactam) have been approved for clinical use in combination with β-lactams such as ceftazidime, imipenem and cilastatin [25][26][27]. Moreover, two novel DBO-type inhibitors, zidebactam and nacubactam, which have high affinity for penicillin-binding protein 2 and potent inhibition of β-lactamase, are under investigation in clinical trials combined with β-lactams [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…IMI/REL gained FDA approval in July 2019, whereas MER/VAB was approved for use in the USA in 2017 [ 266 ]. Interestingly, it has been observed that adding REL, an AVI-like BLI, to IMI can increase the susceptibility of CRE isolates from 8% to 88% to IMI [ 120 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, the imipenem–cilastatin/relebactam (named Recarbrio™, Merck Sharp & Dohme B.V., The Netherlands) combination was approved for the treatment of adults affected by complicated urinary tract infections and complicated intra-abdominal infections [ 26 , 27 ]. The III clinical trials RESTORE-IMI 1 and RESTORE-IMI 2 showed that imipenem–cilastatin/relebactam (I-R) may be used to treat hospital-acquired bacterial pneumonia and ventilator-associated pneumonia caused by non-imipenem susceptible pathogens and atypical mycobacterial infections.…”
Section: Old and New Beta-lactamase Inhibitorsmentioning
confidence: 99%
“…Relebactam is mainly eliminated by urinary excretion [ 4 , 23 , 24 ]. The most common adverse events were nausea (6%), diarrhea (6%), and headache (4%) [ 26 , 27 ]. Unfortunately, the emergence of resistance to imipenem–cilastatin/relebactam combination has been recently described [ 21 ].…”
Section: Old and New Beta-lactamase Inhibitorsmentioning
confidence: 99%